Simulation Study of Single⁃Bubble Ultrasonic Cavitation Dynamics - Jia SUN; Sheng YANG; Kaixuan GUO; Jiao YU (Liaoning Shiyou Huagong Daxue xuebao, 2025)
The kinetic properties of single⁃bubble ultrasonic cavitation are simulated using the finite element analysis software COMSOL Multiphysics. The motion process of a single cavitation bubble driven by ultrasonic sinusoidal, square and triangular waves when vibrating in water is simulated by solving the Rayleigh⁃Plesset model which takes into account the energy viscous loss and the radiation damping caused by the vibration of the spherical bubble, and the curves of the changes of bubble radius, motion velocity and kinetic energy of the bubble wall and pressure within the bubble wall are analyzed.The results show that under the same conditions, the stability of sine wave drive is the strongest; square wave drive has the best cavitation effect but the longest cavitation time; triangular wave shows the weakest cavitation effect. Driven by three types of waves, the kinetic energy of motion of the bubble wall is the largest during the first collapse, and the maximum pressure inside the bubble occurs when the bubble collapses to its minimum radius. The maximum pressure inside the bubble is the greatest when driven by sinusoidal wave compared to square wave and triangular wave.